(untitled) (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2024)
Today, many countries of the world consider the Islamic financial system as a suitable alternative to the traditional economic model. This is due to a number of positive aspects and advantages of the Islamic economic model, including the fact that the Islamic economy is based on real assets, high profitability, low risk of bankruptcy, freedom from riba, compliance with ethical standards and the desire for social support.